A PSAT1 buff of YBX1 transcriptionally sustains HLA-E-mediated evasion of NK immunity - Yangyi Zhang; He Ren; Chaobing Ma; Changhong Shi; Ruigang Yang; Chenxi Wang; Pengfei Feng; Bo Zhang; Chenyu Liu; Zubiao Niu; Yalan Yang; You Zheng; et al. (Proceedings of the National Academy of Sciences, 2025)
Despite great success in certain cancers, immunotherapy made little progress in treating immune cold tumors, largely attributed to an immune-suppressive tumor microenvironment with elusive mechanisms. Here, we report in prostate cancer cells a positive feedback loop driven by phosphoserine aminotransferase 1 (PSAT1) that could be targeted to render effective cytotherapy by natural killer (NK) cells. In the loop, PSAT1 increases Y-box binding protein 1 (YBX1) phosphorylation by microtubule affinity-regulating kinase 2, promoting its nuclear translocation to upregulate PSAT1 transcription. Meanwhile, YBX1 also promotes human leukocyte antigens E (HLA-E) transcription to inactivate NK cells. Consequently, the PSAT1 loop serves as a buff sustaining YBX1/HLA-E expression, suppressing NK killing of prostate cancer cells. Targeting loop molecules, such as PAST1, effectively potentiates tumor suppression by NK cells both in-vitro and in-vivo. Thus, our study uncovered a heretofore unrecognized nonautonomous mechanism for PSAT1, as well as a molecular buff for YBX1, to drive tumor growth by evading NK immunity, providing a promising target for NK cytotherapy of immune cold tumors.